1991
DOI: 10.1111/j.1365-2915.1991.tb00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the possible role of cattle nuisance flies, especially Hydrotaea irritans, in the transmission of summer mastitis in Denmark

Abstract: The summer mastitis pathogens Actinomyces pyogenes, Peptococcus indolicus, Bacteroides melaninogenicus ss. levii, Fusobacterium necrophorum and Streptococcus dysgalactiae were isolated from the polyphagous symbovine dipterans Hydrotaea irritans (Fallén) and Morellia sp. caught around dairy heifers on pasture, but not from the haematophagous species Haematobia irritans (L.), Haematobosca stimulans (Meigen), Culicoides sp. and Simulium sp. Secretions from clinical cases of summer mastitis proved to be sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Infection, however, may take place by exposure of the preputial orifice to feces, manure or moist soil contaminated with these organisms. Insects may also play a role in the transmission of fusobacteria from feces to bison and possibly also from diseased to healthy bison, a mechanism that has been suspected to play a part in the transmission of summer mastitis of cattle in Denmark (Madsen et al, 1991). It has been known for a long time that in most, if not all, cases of necrobacillosis, fusobacteria are found in association with other, usually aerobic bacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…Infection, however, may take place by exposure of the preputial orifice to feces, manure or moist soil contaminated with these organisms. Insects may also play a role in the transmission of fusobacteria from feces to bison and possibly also from diseased to healthy bison, a mechanism that has been suspected to play a part in the transmission of summer mastitis of cattle in Denmark (Madsen et al, 1991). It has been known for a long time that in most, if not all, cases of necrobacillosis, fusobacteria are found in association with other, usually aerobic bacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all species have been isolated from human clinical material. However, Peptoniphilus indolicus can be isolated from cattle, swine and occasionally also be recovered from insects associated with cattle and from human clinical specimens (Ezaki et al , 2001; Madsen et al , 1991); while Peptoniphilus methioninivorax was isolated from retail ground beef (Rooney et al , 2011).…”
mentioning
confidence: 99%
“…Actinomyces pyogenes, Fusobacterium necrophorum and Peptostreptococcus indolicus (Vecht et al 19876;Madsen et al 1992a;Pyorala et al 1992). It has been suggested that certain flies act as vectors for the pathogenic bacteria (Thomas, 1987;Madsen et al 1991), and insect bites and other teat traumas are considered predisposing factors to summer mastitis (Nielsen et al 1987). In addition, different host factors play a role in the establishment and development of the summer mastitis syndrome (Vecht et al 1987 a).…”
mentioning
confidence: 99%